Effectiveness of the Joyful Learning Model with Scratch-Assisted Learning Media on Students' Mathematical Literacy - Natasya Putri Ardhiatul Al Rizky; Elis Nurhayati; Depi Setialesmana (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This study was motivated by students’ mathematical literacy levels that have not yet met expected learning standards and by the limited use of interactive learning media in schools. In addition, studies that combine learning models and digital media to improve students’ mathematical literacy remain limited. This study aimed to examine the effectiveness of a joyful learning model supported by Scratch-based learning media in improving students’ mathematical literacy, as well as to describe students’ mathematical literacy performance, learning activities, and responses during the implementation. The study employed a one-shot case study experimental design. The population comprised all seventh-grade students at SMP Negeri 10 Tasikmalaya, and the sample was Class VII K (n = 32), selected through simple random sampling. Data were collected using a mathematical literacy test, a learning activity observation sheet, and a student response questionnaire. The data were analyzed using a binomial (proportion) test. The results indicated that the joyful learning model supported by Scratch-based media was effective for students’ mathematical literacy, with students’ mathematical literacy categorized as moderate (71.9%). Student learning activities were classified as very good, and students’ responses to the learning were very positive.